Kolaborasi Orang Tua dan Guru untuk Pembelajaran Bahasa Indonesia yang Efektif - Rizka Frasa Kutia; Mutiara Mutiara (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research aims to describe the form of collaboration between schools and parents in improving the learning process of students in elementary, middle and high schools; understand the implementation of collaboration between school management and parents in improving student learning outcomes in elementary, middle and high schools; as well as identifying factors that support and hinder the process of implementing collaboration between school management and parents. This research is a qualitative descriptive research with data collection techniques in the form of interviews, observation and document study. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The research results show that the form and implementation of collaboration between schools and parents includes parenting education, communication and parental involvement. Factors supporting collaboration between schools and parents include professional teaching staff, supporting funds such as BOS funds, and the role of the school committee. Inhibiting factors include limited parental time, parental views about the role of teachers, and low parental self-confidence.